The nature of the symbiotic candidate 2MASS J07363415+6538548 in the field of NGC 2403. Issue 2 (6th October 2020) - Merc, J; Gális, R; Kára, J; Wolf, M; Vrašťák, M
ABSTRACT: New Online Database of Symbiotic Variables includes several poorly characterized objects and candidate symbiotic stars, not only in the Milky Way but also in other galaxies. The goal of the research presented in this paper was to reveal the nature of 2MASS J07363415+6538548, the object discovered as an X-ray source in the field of NGC 2403, and tentatively classified as a symbiotic candidate or a cataclysmic variable. By analysis of available photometric data from ground-based surveys, together with a high-precision photometry from TESS, remarkable astrometric measurements of the Gaia satellite and observations of other surveys spanning from X-rays to infrared, we have found that the object neither not a symbiotic star nor a cataclysmic variable, but rather an active K-type dwarf. The star is located in the distance of 415 pc, has an effective temperature of 4275 K, luminosity of 0.14 L ⊙, mass of 0.7 M⊙, and radius of 0.7 R ⊙ . It has a rotational period ∼ 3 d and is a strong X-ray source with the X-ray luminosity of ∼ 10^30 erg s^-1 . Gyrochronology and isochrone fitting confirmed that the star is young.